Resources Confirmation for Tourism Destinations Marketing Efforts Using PLS-MGA: The Moderating Impact of Semirural and Rural Tourism Destination - Chee, Hua Chin; Lo, May Chiun; Zaidi, Razak; Pooria, Pasbakhsh; Abang Azlan, Mohamad (MDPI, 2020)
This study presents a framework to empirically validate the relationship between the tangible and intangible measures on tourism destination marketing efforts. Uniquely, a case study was developed involving two different nature of tourism destinations (semirural and rural) and is incorporated into the framework to assess its moderating effect on the relationships among the predictors and destination marketing efforts. Two hundred and ninety-three usable responses were collected using a questionnaire survey. Partial least squares structural equation modelling was utilized to perform latent variable and multi-group analyses (MGA). The findings revealed that destination appeal was found to be the biggest concern among tourists visiting semirural and rural tourism destinations in Sarawak. For intangible components, both service quality and destination image were found to be significantly related to destination marketing efforts at a semirural tourism destination. Interestingly, for MGA results, it was worthwhile to learn that the relationship between service quality and destination marketing efforts happened to have a stronger impact on semirural than rural tourism destination. Hence, the proposed framework and research findings from this case study have provided significant insights that help various tourism stakeholders to better strategize and position semirural and rural tourism, particularly in the scenario of Sarawak, Malaysia. Future studies can examine this framework and test at other tourism destinations in Malaysia or in some other countries.